2021
DOI: 10.1016/j.ejca.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on anticancer drug access times between FDA, EMA and the French temporary authorisation for use program over 13 years

Abstract: Introduction: The cancer incidence continues to rise worldwide. Medical innovation has a major impact on patient survival, but within drug development, it can take more than 10 years to obtain marketing authorisation (MA). The time required for access to therapeutic innovation remains critical, so France has developed a specific expanded access program named ATU, which allows the administration of drugs before the European Medicines Agency (EMA) approval. The purpose of this study is to put in perspective the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…First, it suggests that HTA procedures do not necessarily delay patient access to new medicines. This finding builds on earlier work that reported that different early access routes, either privately or publicly funded, offered options to patients in high-income countries . Second, it suggests that frequently used quality indicators of medicine accessibility (eg, time to reimbursement) should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…First, it suggests that HTA procedures do not necessarily delay patient access to new medicines. This finding builds on earlier work that reported that different early access routes, either privately or publicly funded, offered options to patients in high-income countries . Second, it suggests that frequently used quality indicators of medicine accessibility (eg, time to reimbursement) should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 73%
“…This finding builds on earlier work that reported that different early access routes, either privately or publicly funded, offered options to patients in high-income countries. 30,31 Second, it suggests that frequently used quality indicators of medicine accessibility (eg, time to reimbursement) should be interpreted with caution. These indicators are used not only to rank European countries according to their medicine accessibility but also to urge policy makers to improve accessibility.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…6,7 To overcome this delay, France has implemented a specific Early Access Program (EAP) since 1994, allowing patients with unmet medical needs to be treated with an innovative drug before MA. [10][11][12] The Temporary Authorization for Use (ATU) is granted by the French National Agency for Safety of Medicines and Health Products (ANSM) if the assessment of preliminary data presents a positive benefit/risk balance and if the patient has no therapeutic alternatives among the existing therapies/clinical trials. Two types of ATU are available: the nominative ATU, granted for a specific patient at his or her clinician's request; and the cohort ATU, granted for a group of patients who meet specific criteria, for a specific indication, at the pharmaceutical company's request.…”
Section: Introductionmentioning
confidence: 99%
“…This latter stage lasts as long as it takes for the pharmaceutical company and the French Ministry of Health to negotiate and settle on a price and reimbursement, which can be a significant amount of time. The ANSM recently published data showing that, thanks to the ATU program, between 2007 and 2019, 25 out of the 36 oncology drugs (69.4%) that obtained MA had early access with an average of 203 days before Food and Drug Administration (FDA) approval, 428 days before European Medicines Agency (EMA) approval, and 566 days before national public reimbursement 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation